Evaluation of the A/Seal/Mass/1/80 virus in squirrel monkeys. - Murphy, B R (1983)
An influenza A virus isolated from seals [A/Seal/Mass/1/80 (H7N7)] and an isolate of this virus obtained from a human conjunctiva were evaluated for replication and virulence in squirrel monkeys. When the seal virus was administered intratracheally, it replicated in lungs and nasopharynges and induced illness almost to the same extent that a human influenza A virus [A/Udorn/72 (H3N2)] did. In one monkey that died of pneumonia, the seal virus was recovered from spleen, liver, and muscle as well as lung. After conjunctival administration in monkeys, the seal virus replicated to a peak titer in the conjunctivae 30-fold greater than that attained by the human virus, but this difference was not statistically significant. In contrast, the seal virus replicated less well than the human virus in the tracheae and nasopharynges when administered by the conjunctival route. These results indicate that the seal virus can replicate efficiently in primates, that it can spread systemically, and that it might differ from human virus in being able to replicate slightly better in primate conjunctival tissue.